EKSISTENSI WEB SERIES YOUTUBE DALAM INDUSTRI PERFILMAN DI INDONESIA - Sinta Lestari (ULTIMA Comm, 2022)
This study explores audience interactivity and change, motivation and satisfaction of web series creators, and the preservation of YouTube as a YouTube Web Series Creative Channel as part of the presence of web series in the film industry in the case study. While the research subject is a producer of YouTube Web Series from Production House (PH) PIM Pictures. Data collection is done through interviews. At the interview stage of this research, the answers are then recorded according to the series of questions that will be discussed. In addition, this study also collects, and examines any data with sources related to the research problem. Based on the results of data analysis obtained in in-depth interviews with Digital Production House Pim Pictures, it can be understood that there are research results, namely the existence of web series in the film industry in Indonesia is the existence of interactivity and change in the audience. second, the motivation of web series creators is for personal interest, providing information, and fulfilling entertainment, existence, satisfaction to introduce before to the big screen. The first source of satisfaction for Web Series creators identified was YouTube-facilitated exposure in the context of social media platforms. third, the promotion of YouTube as a YouTube Web Series Creative Channel allows its users to innovate and create new and independent web series.